Modeling of data retention statistics of phase-change memory with confined- and mushroom-type cells. (August 2016) - Kwon, Yongwoo; Park, Byoungnam; Yang, Heesun; Hwang, Jin-Ha; Kang, Dae-Hwan; Jeong, Hongsik; Song, Yunheub
Abstract: Data retention statistics of phase-change memory with two representative cell schemes, confined and mushroom cells, were investigated using phase-field method that can correctly model successive nucleation events and their growth, simultaneously. Several directions of cell structure engineering are suggested. An interesting point is that reducing only one lateral dimension below a characteristic length can improve the data retention. Most importantly, it was found that the cumulative distribution of the retention time is Weibull for the mushroom cells while that is lognormal for the confined cells. Highlights: Retention failure of phase-change memory occurs by the spontaneous crystallization of the active material. The crystallization including stochastic nucleation was modeled by phase-field method. Behaviors of the median and spread of the retention time were quantitatively analyzed for different cell structures. The retention time distribution is lognormal for the confined cells while that is Weibull for the mushroom cells.